NAHDLATUL ULAMA AND ITS COMMITMENT TOWARDS MODERATE POLITICAL NORMS: A COMPARISON BETWEEN THE ABDURRAHMAN WAHID AND JOKOWI ERA - Alexander Arifianto (Journal Of Global Strategic Studies, 2021)
This article addresses recent development related to Nahdlatul Ulama (NU) – Indonesia’s largest Islamic organization - and its recent actions as it faces ideological and political challenges from other conservative Islamist organizations. In the process, NU seems to have engaged in backtracking its commitment to consistently promote moderate norms like democracy and tolerance toward different religious and political viewpoints. It examines the factors which explains this reversal and answers the following research puzzle: Under which socio-political conditions do a religious organization that has adhered to follow moderate political norms and discourses decide to backtrack from them and decide to pursue policies to embrace an ‘exclusivist moderation’? The article concludes the declining commitment to moderate norms within the NU is due to growing ideological competition from conservative Islamists both within and outside of the organization, leading NU to embrace immoderate responses to crack down against its competitors.